PERANCANGAN STRATEGI KOMUNIKASI PEMASARAN TERPADU (IMC) DALAM MENDORONG KONVERSI PENGGUNAAN PRODUK BY.U BY TELKOMSEL SEBAGAI SPONSORSHIP & CREATIVE DIRECTOR - Tegar Ilham Hamzah; Yohanes Thianika Budiarsa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
by.U is a digital cellular service launched by Telkomsel that targets Generation Z and youngdigital users. Despite being positioned as a digital service provider oriented toward youth, thelevel of by.U usage among senior high school (SMA) and vocational high school (SMK) studentsin Semarang remains relatively low. The survey results of 814 students show that only 5.7% (46students) are active users of the by.U SIM card; the perceived risk level of the service is 52.2%;and purchase intention remains low at 20.8%. Therefore, an integrated marketingcommunication campaign was designed through the programs “by.U On The Move” and “by.UInter-School Digital Challenge.” The campaign adopts an Integrated MarketingCommunication (IMC) approach. This communication strategy was developed to graduallymove the audience through the stages of attention, interest, desire, and action, following theHierarchy of Effects. The results of the campaign implementation indicate significant changesin audience responses. The level of perceived risk decreased to 19.5%, while purchase intentionincreased to 118 students. A Sponsorship and Creative Director was responsible forapproaching potential sponsors and securing partnerships, as well as capturing and editingvisual content for all campaign needs.